The impact of GnRH-agonist triggers on autologous in vitro fertilization outcomes: A retrospective analysis - Oosthuizen, Lizle (Department of Obstetrics and Gynaecology, 2021)
BACKGROUND: In vitro fertilization in assisted reproduction requires controlled ovarian stimulation with exogenous gonadotrophins and oocyte maturation before ultrasound guided aspiration. GnRH-agonists have been utilized as an alternative to hCG for oocyte maturation prior to follicle aspiration. GnRH-agonist triggers are proven to lower ovarian hyperstimulation syndrome risk, a condition that can be life threatening. Lower pregnancy rates have been reported in the literature with the GnRH-agonist trigger, leading to recommendations of elective embryo cryopreservation, delayed transfer and increased costs to the patient. AIM: To determine if intensive luteal phase support of GnRH-agonist triggered cycles with intramuscular progesterone and oral oestrogen can result in similar pregnancy rates when comparing fresh embryo transfer outcomes with those of hCG triggered cycles. STUDY DESIGN, SIZE, DURATION: The study was a retrospective analysis of 279 fresh embryo transfers in autologous IVF cycles, which took place over the period of one year at Cape Fertility Clinic in Cape Town. RESULTS: Biochemical (49.40% vs 41.84%), clinical (43.37% vs 36.22%) and ongoing pregnancy rates (37.35% vs 33.16%) were higher in the GnRH-agonist triggered arm in comparison to the hCG triggered arm, respectively. Miscarriage rates were similar at 24.29% in the GnRH-agonist arm, versus 20.73% in the hCG triggered arm. None of the results were statistically significant. CONCLUSION: Similar pregnancy rates can be achieved with both hCG and GnRH-agonist triggered IVF cycles by supporting the GnRH-agonist triggered luteal phase with intensive intramuscular progesterone support.